Artificial Intelligence and Discretionary Decisions. The Triumph or Loss of Commander Pirx? - Dubiński, Łukasz (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2021)
The aim of the considerations is to determine whether artificial intelligence units can take the place of humans in administrative proceedings ending with the issuance of discretionary decisions. The author starts from presenting the essence of discretionary decisions and guide the scope of judicial control over them. The presented considerations relate primarily to the potential placement of such devices in the “administrative justice system” that can be defined as artificial intelligence units in the strict sense. Therefore, this concerns devices for which human intervention is usually limited to switching on and technical supervision. However, the considerations can also be applied to such devices where human interference in their operation is slightly greater. It should be emphasized, however, that it this does not concern devices that are fully or almost fully controlled by humans.